Automated Tool‐Path Generation for Rapid Manufacturing of Additive Manufacturing Directed Energy Deposition Geometries. Issue 11 (8th May 2020) - Biegler, Max; Wang, Jiahan; Kaiser, Lukas; Rethmeier, Michael
Abstract : In additive manufacturing (AM) directed energy deposition (DED), parts are built by welding layers of powder or wire feedstock onto a substrate with applications for steel powders in the fields of forging tools, spare parts, and structural components for various industries. For large and bulky parts, the choice of tool‐paths influences the build rate, the mechanical performance, and the distortions in a highly geometry‐dependent manner. With weld‐path lengths in the range of hundreds of meters, a reliable, automated tool‐path generation is essential for the usability of DED processes. This contribution presents automated tool‐path generation approaches and discusses the results for arbitrary geometries. So‐called "zig‐zag" and "contour‐parallel" processing strategies are investigated and the tool‐paths are automatically formatted into machine‐readable g‐code for experimental validation to build sample geometries. The results are discussed in regard to volume‐fill, microstructure, and porosity in dependence of the path planning according to photographs and metallographic cross‐sections. Abstract : This contribution presents automated tool‐path generation approaches for directed energy deposition additive manufacturing and discusses the results for arbitrary geometries. So‐called "zig‐zag" and "contour‐parallel" processing strategies are investigated for shape accuracy, pore formation, and microstructure. Recommendations are given for the strengths and weaknesses of both algorithms in regard to the shapes that need to be filled.